Questions of context: reading a century of German mission theology - Flett, John G. (Missiological engagements, 2020)
Introduction: Is It Possible to Abandon Contextualization? -- At the Beginning of German Mission Theory -- Grounded in the Orders of Creation -- Eschatology and Agency -- The Widening of Horizons -- Hermeneutics, Communication, and Translation -- Intercultural Theology -- Conclusion: The Proper Complexity of Context